PENGARUH PEMBERIAN BIOURINE SAPI PADA SISTEM HIDROPONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT - I Putu Sujana; Putu Lasmi Yuliyanthi Sapanca; Ni Putu Eka Pratiwi; I Gusti Ngurah Alit Wiswasta; Ignasius Sandriawan (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
This study aims to determine the effect of giving different cow biourine on the hydroponic system to get the best growth and yield of land kangkung plants. The design used in this study was a randomized block design (RAK). With 6 treatments of giving cow biourine, K1: cow biourine giving 100 ml/1 liter of water, K2: giving 200 ml/1 liter, K3: giving 300 ml/1 liter, K4: given 400 ml/1 liter, K5: given 500 ml/1 liter and K6: given 600 ml/1 liter of water. With 4 replications and 24 trials. The results of the research on the effect of giving cow biourine on growth parameters and yields of land kangkung in a hydroponic system showed a very significant effect on all parameters. The conclusion of this study was that the highest yield was obtained by giving biourine 300 ml/1 liter of water such as the highest plant height (K3 = 45.80 cm), the highest number of leaves (K3 = 15.00 pieces), leaf area (K3=102.25 cm), total wet weight of plants (K3=40.03 g) and oven-dry weight of plants (K3=2.19 g). giving biorine 300 ml/1 liter of water is the right way to get the best yield of land kangkung in a hydroponic system compared to giving 100 ml/1 liter of water; administration of 200 ml/1 liter of water; administration of 400 ml/1 liter of water; administration of 500 ml/1 liter of water; administration of 600 ml / 1 liter of water.